The influence of polydopamine coating on gold nanorods for laser desorption/ionization time-of-flight mass spectrometric analysis - Kang, Kyungtae; Jang, Hongje; Kim, Young-Kwan (Royal Society of Chemistry, 2017)
This paper examines the effect of polydopamine (PD) coating of gold nanorods (GNRs) on their performance as a matrix material for laser desorption/ionization time-of-flight mass spectrometry (LDI-TOF-MS) analysis. Bare GNRs and PD-coated GNRs (PD@GNRs) were utilized for LDI-TOF-MS analyses of small molecules and synthetic polymers, and the influences of PD-coating were mechanistically studied. Based on the results, we found that the PD-coating of GNRs suppressed the generation of undesired gold cluster ions, enhanced photothermal conversion and the LDI-TOF-MS efficiency, and expanded the working molecular weight range.
Keywords: SMALL MOLECULES; GRAPHENE OXIDE; NANOPARTICLES; MS; SENSITIVITY; ENRICHMENT; MATRIX; TISSUE; FILMS